2018
DOI: 10.1038/s41467-018-03292-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-catalytic hydrogenation of VO2 in acid solution

Abstract: Hydrogenation is an effective way to tune the property of metal oxides. It can conventionally be performed by doping hydrogen into solid materials with noble-metal catalysis, high-temperature/pressure annealing treatment, or high-energy proton implantation in vacuum condition. Acid solution naturally provides a rich proton source, but it should cause corrosion rather than hydrogenation to metal oxides. Here we report a facile approach to hydrogenate monoclinic vanadium dioxide (VO2) in acid solution at ambient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
130
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(137 citation statements)
references
References 37 publications
7
130
0
Order By: Relevance
“…The results showed that the Peierls V-V dimerization was less pronounced in HVO 2 than in M-VO 2 , but electrons supplied by hydrogens expanded the lattice through an electron-lattice coupling, which seemed to trigger a stronger electron correlation in narrow d bands and created the band gap in the insulating HVO 2 phase. Recently, Chen et al 79 reported a facile approach to hydrogenate monoclinic VO 2 in an acidic solution under ambient conditions by placing a small piece of low-workfunction metal (Al, Cu, Ag, Zn, or Fe) on the VO 2 surface. Additionally, the later successful doping of Li + into VO 2 suggests a general atomic doping approach of using a proton or cation solvent source together with electrons from metals.…”
Section: Elemental Dopingmentioning
confidence: 99%
“…The results showed that the Peierls V-V dimerization was less pronounced in HVO 2 than in M-VO 2 , but electrons supplied by hydrogens expanded the lattice through an electron-lattice coupling, which seemed to trigger a stronger electron correlation in narrow d bands and created the band gap in the insulating HVO 2 phase. Recently, Chen et al 79 reported a facile approach to hydrogenate monoclinic VO 2 in an acidic solution under ambient conditions by placing a small piece of low-workfunction metal (Al, Cu, Ag, Zn, or Fe) on the VO 2 surface. Additionally, the later successful doping of Li + into VO 2 suggests a general atomic doping approach of using a proton or cation solvent source together with electrons from metals.…”
Section: Elemental Dopingmentioning
confidence: 99%
“…This is attributed to the thermal-induced crystal phase transition of VO 2 . 34,35 Upon increasing temperature, the crystal phase changes from insulating monoclinic to metallic rutile states, releasing the free electrons to support the plasmon resonance, resulting in an increased absorption in the NIR region. In addition, an LSPR red-shift is observed when temperature is increased (Figure 2A), which is consistent with the previous report on 2D-patterned VO 2 NPs on quartz substrates.…”
Section: Active Localized Surface Plasmon Resonancesmentioning
confidence: 99%
“…This H atom insertion induced the metallic VO 2 phase at room temperature (Supporting Information, Figures S2, S3). This AA/AA‐Na absorption‐induced metallic VO 2 film is stable in acid solution, exhibiting excellent anti‐corrosion property in 15 wt % H 2 SO 4 solution (Supporting Information, Figure S4) and nearly intact AFM images (Supporting Information, Figure S5). Furthermore, the H‐doped VO 2 films exhibit no sharp MIT behavior even within the low temperature range (Supporting Information, Figure S6).…”
Section: Figurementioning
confidence: 99%
“…The sample treated by 6 h shows the diffraction peak at about 39.6° which is readily indexed to tetragonal rutile VO 2 (R) structure (JCPDS# 79‐1655). Raman spectra in Figure b shows the typical characteristic peaks at 191 cm −1 , 221 cm −1 , 308 cm −1 , 618 cm −1 for the pristine insulating states, all of which disappear after 6 h treatment (Figure b), further confirming the crystal structure transformation to tetragonal rutile‐like structure (metallic state) . With less treating time of about 2 h, several smaller characteristic peaks for pristine VO 2 suggest the coexistence two phases due to the gradual diffusion of H‐atoms along the film depth direction.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation